2017
DOI: 10.1007/s11307-017-1123-5
|View full text |Cite
|
Sign up to set email alerts
|

Combined PET/MRI: Global Warming—Summary Report of the 6th International Workshop on PET/MRI, March 27–29, 2017, Tübingen, Germany

Abstract: The 6th annual meeting to address key issues in positron emission tomography (PET)/magnetic resonance imaging (MRI) was held again in Tübingen, Germany, from March 27 to 29, 2017. Over three days of invited plenary lectures, round table discussions and dialogue board deliberations, participants critically assessed the current state of PET/MRI, both clinically and as a research tool, and attempted to chart future directions. The meeting addressed the use of PET/MRI and workflows in oncology, neurosciences, infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 78 publications
(60 reference statements)
1
41
0
Order By: Relevance
“…Thus, artifacts are mostly easily detectable in MR-AC, indicating regions of potentially inaccurate PET quantification [45,54]. ▪ While new features for the improvement of MR-AC are constantly developed and implemented into the commercial software of available PET/MRI systems, including high-resolution Dixon AC, ultrashort echo time (UTE), zero TE (ZTE) sequences and/or bone models for bone detection in PET/MRI attenuation correction [17,34,40,41], users need to remain attentive to MR-AC related limitations and artifacts in SUV quantification. ▪ Truncation artifacts along patient arms in MR-AC may affect PET quantification.…”
Section: Artifactsmentioning
confidence: 99%
“…Thus, artifacts are mostly easily detectable in MR-AC, indicating regions of potentially inaccurate PET quantification [45,54]. ▪ While new features for the improvement of MR-AC are constantly developed and implemented into the commercial software of available PET/MRI systems, including high-resolution Dixon AC, ultrashort echo time (UTE), zero TE (ZTE) sequences and/or bone models for bone detection in PET/MRI attenuation correction [17,34,40,41], users need to remain attentive to MR-AC related limitations and artifacts in SUV quantification. ▪ Truncation artifacts along patient arms in MR-AC may affect PET quantification.…”
Section: Artifactsmentioning
confidence: 99%
“…Despite the outlined complexity of the topic, I like to conclude with a statement from the 6 th Tübingen International Workshop on PET/MR: “There was general agreement between the participants and many clinical users that MRAC has been solved to the degree required for clinical use based on accepted image metrics.” This statement is supportive of my view: we have the tools and methods for accurate and robust clinical use of PET/MR already at hand. Given the mentioned broad variety of MRAC methods, there is, however, further need toward quality control and standardization efforts in PET/MR AC .…”
Section: Against the Proposition: Harald H Quick Phdmentioning
confidence: 99%
“…variable amounts of mutational Kras (24) and the likelihood of ongoing transitional processes, entropy as a continuous variable can be imagined as a non-invasive "sensor" of such events that correlates with the extent of basal-like regions within a particular tumor. The testing of such hypotheses is challenging, requiring an integrated whole-tumor analysis, including high data-rich imaging, histopathology and molecular profiling(25).The rapid evolution of new therapeutic options in the treatment of PDAC requires the development of markers for a reliable pre-therapeutic patient stratification and -in light of the above-mentioned plasticity, therapy monitoring. Conroy et al demonstrated significantly improved survival rates of FOLFIRINOX over Gemcitabine monotherapy in the palliative setting…”
mentioning
confidence: 99%